Gladchenko A.N., Shevelya V.V., Kianycia E.V., Zverlin V.G. Wear out capability of filed polymers subject to their processing in extruder. - Гладченко, А.Н.; Шевеля, В.В.; Кияница, Е.В.; Зверлин, В.Г. (Problems of Tribology, 2014)
The basic factors, that define the operation life of the equipment for the processing of polymer materials, are wear resistance of operative parts and wear out capability of filled polymer materials. Mathematic model on the basis of fatigue conception of the wear of metals by abrasive, fixed in the polymer matrix, that are possessed of viscoelastic properties was built. This model allows to bind wear resistance of alloy materials and their rheological properties. The rheological index that characterizes elasto-plastic properties of wearing material was introduced for consideration. The experimental verification of the model was examined on the iron alloys of nickel, cobalt as well as on hard alloys. The dependence of wear rate of mentioned alloys on relative solidity of the polymer fillers with regard to the process of treatment in extruders was studied.